A Syntactic Analysis Of Noun Phrases Found In George Bernard Shaw's 'Arms And The Man' (Using X-Bar Approach) - Suhendro, Ihwan Rosidi; , Dra. Malikatul Laila, M.Hum; , Siti Fatimah, S.Pd, M. Hum (2013)
This study deals with analyzing drama script using X-bar approach in representative of tree-diagram of Andrew Radford's book (1988). This study aims at identifying and describing the constituent of Noun Phrase and the dominant construction of Noun Phrase found in George Bernard Shaw's 'Arms and the Man'. This research applies descriptive qualitative method. The objects are Noun Phrases constituent, and the analyzed data are sentences and/or phrases containing Noun Phrase construction used in 'Arms and the Man' drama script. The whole data are 178 data found by the writer. Based on the analysis, the writer found that there are thirty-five constructions of Noun Phrase and the dominant constructions lies within pre-modifier + Noun (Head) construction. For specific result, the writer provides the percentage in detail, such as Noun, in 3 data (1, 7%), Premodifier + Noun (Head), in 94 data (52, 8%), Noun (Head) + Post-modifier, in 5 data (2, 8%), Pre-modifier + Noun (Head) + Post-modifier, in 76 data (42, 7%). From research finding, the writer concludes that there are thirty-five constituents and constructions of Noun Phrase in English language. Sometimes Noun Phrase has Prepositional Phrase as the post-modifier. Every PP has status in Noun Phrase either as complement (obligatory) or adjunct (optional). It can be observed by paraphrasing the head noun into transitive verb (Vt).